T-lymphocyte profile as a predictive marker for placental retention in buffalo (Bubalus bubalis) - SINGH, PRAHLAD; SHARMA, R D; NANDA, A S; SINGH, HARMEET (The Indian Journal of Animal Reproduction, 2023)
Peripheral blood lymphocyte profile was assessed in buffaloes with normal placental separation(n=5) and those with retention of placenta (n=5). Jugular venous blood samples (30 ml) were collectedfrom every buffalo on 1 to 10 days pre partum, day of calving and on 1 to 10, 15, 20, 25 and 30 day postpartum. T-Iymphocyte profile was evaluated, with respect to, per cent peripheral blood lymphocytesheep red blood cell-rosettes (SRBC-R). Plasma vitamin-A, b-carotene, vitamin - E and zinc wereestimated for every subject on the sampling days, by standard methods. Significant (P
Keywords: Retained Placenta; T-lymphocytes; vitamin A; bita-carotene; vitamin E; zinc; buffalo